REPRESENTASI DOMINASI PEREMPUAN DALAM FILM THE SHADOW STRAYS: ANALISIS SEMIOTIKA JOHN FISKE - Muhammad Hilman Zafiri; Ririn Puspita Tutiasri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study analyzes the representation of female dominance in the 2024 Netflix film The Shadow Strays, directed by Timo Tjahjanto, using John Fiske's semiotic approach encompassing three levels of analysis: reality, representation, and ideology. The film features a female protagonist, Nomi, a hired assassin who dominates masculine spaces within the action genre. Through analysis of 23 selected scenes covering visual, cinematographic, and narrative elements, this study finds that female dominance is consistently represented through masculine costuming and makeup, camera techniques positioning women in strategic and superior roles, and dialogue that systematically subverts patriarchal expectations. At the ideological level, the film advances feminist values by depicting an organization entirely led by women and moral conflicts resolved without male intervention. This study contributes to understanding how film media shapes public discourse on gender equality, particularly through the representation of female masculinity in contemporary Indonesian cinema, while offering insights for the film industry to continue producing strong, ideologically grounded narratives centered on women.